Analisis Fenomena Praktik Money Game pada Aplikasi Trading Investasi Menurut Perspektif Islam - Siti Salbiah; Hendri Tanjung; Abristadevi Abristadevi (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The rise of binary options trading, especially the OctaFX application, in carrying out buying and selling financial assets. Whether it's buying and selling foreign currency (forex), stocks, derivatives, to cryptocurrencies (cryptocurrency). practice money game and the views of Islamic law by using three sharia rule guidelines (AAOIFI Standards, MUI Fatwa, and POJK). Thus, it can determine the suitability of binary options trading with sharia law. In this study, the author uses a descriptive qualitative method of content analysis in which the data source is taken from news related to the object of research, namely the case of phenomena that occur in the OctaFX application from the period 2021 to early 2022. The data will be analyzed using content analysis , namely by adjusting the data obtained with the basic guidelines of sharia rules. The extent of compliance with sharia law on binary options trading on the OctaFX application. Based on the results of research conducted and explained by the author that trading practices on the OctaFX application are still far from conforming to sharia rules, as well as the existence of elements of money game which are characterized by the absence of legality in the application, the presence of gharar elements, and not in accordance with the rules of muamalah law. Keywords: Money Game Practice, OctaFX Trading, Islamic Perspective